Very Early Onset Inflammatory Bowel Disease: A Clinical Approach With a Focus on the Role of Genetics and Underlying Immune Deficiencies. Issue 6 (3rd December 2019) - Ouahed, Jodie; Spencer, Elizabeth; Kotlarz, Daniel; Shouval, Dror S; Kowalik, Matthew; Peng, Kaiyue; Field, Michael; Grushkin-Lerner, Leslie; Pai, Sung-Yun; Bousvaros, Athos; Cho, Judy; Argmann, Carmen; et al.
Abstract : Very early onset inflammatory bowel disease (VEO-IBD) reflects IBD presenting before 6 years of age. We provide an approach to diagnosis and management of patients with VEO-IBD, based on expert opinion from members of the VEO-IBD Consortium (www.VEOIBD.org ). Abstract: Very early onset inflammatory bowel disease (VEO-IBD) is defined as IBD presenting before 6 years of age. When compared with IBD diagnosed in older children, VEO-IBD has some distinct characteristics such as a higher likelihood of an underlying monogenic etiology or primary immune deficiency. In addition, patients with VEO-IBD have a higher incidence of inflammatory bowel disease unclassified (IBD-U) as compared with older-onset IBD. In some populations, VEO-IBD represents the age group with the fastest growing incidence of IBD. There are contradicting reports on whether VEO-IBD is more resistant to conventional medical interventions. There is a strong need for ongoing research in the field of VEO-IBD to provide optimized management of these complex patients. Here, we provide an approach to diagnosis and management of patients with VEO-IBD. These recommendations are based on expert opinion from members of the VEO-IBD Consortium (www.VEOIBD.org ). We highlight the importance of monogenic etiologies, underlying immune deficiencies, and provide a comprehensive description of monogenic etiologies identified to date that are responsible for VEO-IBD.